Building SMEs’ Competitive Advantage and the Organizational Agility of Apparel Retailers in Indonesia: The role of ICT as an Initial Trigger - Achsanul Qosasi; Erwin Permana; Anang Muftiadi; Margo Purnomo; Erna Maulina (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
The use of Information and Communication Technology (ICT) could make Small Medium Enterprises (SME) capable of capturing future potential markets. This study investigates how the use of ICT affects firms’ agility and finally ends in their competitive advantage. In other words, this study examines how firms’ ICT capabilities directly enhance their competitive advantage. Their ICT capability also affects the firms’ competitive agitlity indirectly by mediating their business agility. This study infers that if small business firms would like to enhance their supply chains and customer relationship management, they should adopt ICT as a tool to transform their businesses. This transformation improves small firms’ competitiveness levels because it allows them to manage all their customers. Meanwhile, the small business firms could enhance their agility due to their suppliers’ closeness. This means that the small business firms have posited the concepts and philosophy suggested by the resources dependent theory.